Midnight black [large type] - Greaney, Mark (Greaney, Mark. Gray Man novel, 2025)
"With his lover imprisoned in a Russian gulag, the Gray Man will stop at nothing to free her in this latest entry in the #1 New York Times bestselling series. A winter sunrise over the great plains of Russia is no cause for celebration. The temperature barely rises above zero, and the guards at Penal Colony IK22 are determined to take their misery out on the prisoners--chief among them, one Zoya Zakharova. Once a master spy for Russian foreign intelligence, then the partner and lover of the Gray Man, she has information the Kremlin wants, and they don't care what they have to do to get it. But if they think a thousand miles of frozen wasteland and the combined power of the Russian police state is enough to protect them, they don't know the Gray Man. He's coming, and no one's safe."--